2020
DOI: 10.1093/beheco/arz186
|View full text |Cite
|
Sign up to set email alerts
|

Males evolve to be more harmful under increased sexual conflict intensity in a seed beetle

Abstract: One conspicuous manifestation of sexual conflict is traumatic mating, in which male genitalia damage the female during copulation. The penis of the seed beetle, Callosobruchus maculatus, is covered in spines that damage the female reproductive tract. Females kick males ostensibly to shorten these harmful copulations. How these iconic conflict behaviors coevolve in response to sexual conflict intensity can provide insight into the economics of these traits. We examined whether male harm and female resistance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Our study provides evidence that genital coevolution may be triggered by changes in one sex, and the resulting precedence pattern may persist at long time scales. Although empirical evidence in favour of either male‐ or female‐driven coevolution is to date elusive, experimental studies seem to indicate that increased sexual conflict tends to affect male morphology earlier (Cayetano et al., 2011; McNamara, Sloan, Kershaw, & Lieshout, 2020). In contrast, here we found that the vast majority of changes to membranization in females departed from the ancestral form, whereas transitions in the male proctiger were overwhelmingly contingent on preceding female changes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides evidence that genital coevolution may be triggered by changes in one sex, and the resulting precedence pattern may persist at long time scales. Although empirical evidence in favour of either male‐ or female‐driven coevolution is to date elusive, experimental studies seem to indicate that increased sexual conflict tends to affect male morphology earlier (Cayetano et al., 2011; McNamara, Sloan, Kershaw, & Lieshout, 2020). In contrast, here we found that the vast majority of changes to membranization in females departed from the ancestral form, whereas transitions in the male proctiger were overwhelmingly contingent on preceding female changes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This was expected because the reduction of conflict should favour less harmful males and females that are less resistant to male harm. Other experimental evolution studies under altered mating systems have been performed in dung flies Martin & Hosken, 2003), different species of fruit flies (D. melanogaster; (Gerrard et al, 2013;Hollis et al, 2014;Innocenti et al, 2014;Perry et al, 2016); D. pseudoobscura; (Crudgington et al, 2005); D. serrata; (Chenoweth et al, 2015) , seed beetles (McNamara et al, 2020) and hermaphroditic flatworms (Janicke et al, 2016). Though aspects of the treatments differ amongst such experiments, some common patterns have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…2015]), seed beetles (McNamara et al. 2020), and hermaphroditic flatworms (Janicke et al. 2016).…”
mentioning
confidence: 99%